Chromene–triazole-pyrimidine based chemosensor therapeutics for the in vivo and in vitro detection of Fe3+ ions. (30th March 2021) - Shamsiya, Aranhikkal; Bahulayan, Damodaran
Abstract : MCR and click synthesis of selective and sensitive Fe 3+ sensors that can interact with CDK2 proteins and cytotoxicity against the human cervical cancer cell line HeLa is developed. Abstract : The development of a series of chromene–pyrimidine triad molecules for the selective detection of Fe 3+ is described. The new chemosensors were synthesized through the sequential use of multicomponent reactions (MCRs) and click chemistry marking its ease and cost effectiveness. The sensor molecules showed turn-off fluorescence towards Fe 3+ with an extremely low limit of detection (LOI) and a strong affinity to cancer causing CDK2 proteins with binding energy closer to −9.8 kcal mol −1 as indicated by the molecular docking studies. The free hydrophilic handles present on the sensors are advantageous for binding with cellular Fe 3+ demonstrating the potential of these molecules as therapeutics for iron overloading diseases. The therapeutic potential is further illustrated via cytotoxicity studies against the human cervical cancer cell line HeLa, which showed a very low IC50 value of 15 μg mL −1 .